Essential Grammar in Use : A self-study reference and practice book for elementary learners of English - Murphy, Raymond (Cambridge University, 2015)
Grammar in Use is the world's best-selling grammar series for learners of English. Essential Grammar in Use with Answers, authored by Raymond Murphy, is the first choice for elementary-level (A1-B1) learners and covers all the grammar required at this level. It is a self-study book with simple explanations and lots of practice exercises, and has helped millions of people around the world to communicate in English. It is also trusted by teachers and can be used as a supplementary text in classrooms.